Become Smart Parents In Parenting ASD Children By Following Parenting Seminars - Novia Nuril Firdaus; Faktianda Okta Zulfikar; Luqyana Dhiya Amira; Arum Sekar Kinasih; Rosa Auralia Wulandari; Ediyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article was written as a report related to a leadership project assignment which is one of the courses in the Pre-service PPG program. The leadership project activities carried out are community service activities designed in parenting ministries. The parenting seminar aims to add insight and knowledge to parents in terms of parenting children with ASD according to their developmental stages and characteristics. The seminar method is carried out by conveying information based on research results followed by discussion activities by all participants in the activities. The implementation of activities is carried out in a hybrid manner, namely face-to-face and online. The goal is that activity participants do not only include guardians of students at the UM Laboratory Autism SLB, but have a wider range of participants. In general, the hope of implementing this activity is to increase parents' knowledge and skills in terms of good and appropriate parenting for children with ASD